Social Construction & Tri Hita Karana Concept: Transformation of Philanthropy Practice for Community Wellbeing - Budianto, Mahmud; Lomi, Ruben; Setiawan, I Wayan Arta; Widhiastini, Ni Wayan; Permatasari, Ni Putu Intan (The Indonesian Journal of Social Studies, 2020)
Globalization has caused a local-scale value system to move along with the accelerating rate of globalization being accepted as a universal value system. One is philanthropy, practiced by various institutions and social organization. Tri Hita Karana as a relational concept of human relations, environment and God prevailing in Bali, it is interesting to observe through the construction pattern social which includes institutionalization, legitimacy and socialization. The purpose of this study is to contribute critically, holistically and comprehensively on philanthropic practices in cooperation social responsibility programs carried out through social construction. This study used a qualitative method with a purposive determination of informants. The results showed that the social construction of Tri Hita Karana was carried out on the practice of philanthropy through the pattern of institutionalization, legitimacy and socialization.